Quorum quenching activity of indigenous quorum quenching bacteria and its potential application in mitigation of membrane biofouling. Issue 5 (3rd January 2018) - Gu, Yanling; Huang, Jinhui; Zeng, Guangming; Shi, Yahui; Hu, Yi; Tang, Bi; Zhou, Jianxin; Xu, Weihua; Shi, Lixiu
Abstract: BACKGROUND: Quorum sensing (QS) could regulate gene expression so as to mediate some bacterial behaviors such as the production of extracellular polymeric substances (EPS) and biofilm formation. In this study, a quorum quenching (QQ) bacterium was isolated from an indigenous lab‐scale membrane bioreactor (MBR) and encapsulated in a dumpling‐shaped microbial bag for biofouling control. RESULTS: This QQ bacteria has a higher genetic homology with Acinetobacter bereziniae strain. The effect of time and temperature on the QQ activity of the microbial bag was tested by degrading N‐acyl homoserine lactone (AHL). The results showed the degradation of C8‐HSL (N‐Octanoyl‐DL‐homoserine lactone) and C6‐HSL (N‐Hexanoyl‐L‐homoserine lactone) could reach equilibrium within 2 h. In addition, a suitable temperature for AHL degradation was 20 °C, at which the rate of degradation of C6‐HSL and C8‐HSL by the microbial bag was 88% and 69%, respectively. The antifouling efficiency of the microbial bag was investigated by a constant pressure filtration system. With the microbial bag added, the decrease of permeability was obviously improved. After 14 days, the permeability with QQ decreased to 18% while the control experiment exhibited almost no permeability. CONCLUSION: The excellent AHL degradation rate and the filtration test showed that this QQ bacteria has an excellent antifouling potential in membrane filtration systems. © 2017 Society of Chemical Industry